Effects of spinal mobilization techniques in the management of adolescent idiopathic scoliosis - A meta-analysis - Farooqui, Sumaira Imran; Siddiqui, Pirzada Qasim Raza; Ansari, Basit; Farhad, Ali (International Journal of Health Sciences, 2018)
Objectives: The aim of this study is to examine the effectiveness of diverse exercise regimes used in multiple Randomized Control Trials as the only conservative management strategy for increased Cobb angle among Adolescent Idiopathic Scoliosis. Methods: Database such as Google Scholar, Medline, and BioMed Central was reconnoitered for the purpose of research articles of interest. Studies in which the effects of conservative management of scoliosis on the magnitude of Cobb angle were calculated were scrutinized procedurally, studies fulfilling the inclusion criteria were retrieved and encompassed in the present study. Result: A total of 698 cases of AIS that were included in 17 controlled trials are part of this meta-analysis. The pool effects were measured using a standardized mean difference between the experimental and control group at 95% of confidence interval using Hedges’g statistics. Outcomes analyzed, reveals favorable for exercises based experimental group in term of standardized mean difference with an impact of 0.42° on random effect model, according to a Cohen’s rule of thumb that depicts a near to moderate effects of exercises based interventions on Cobb angle. Conclusion: The present study concludes that therapeutic exercise regimes alone have a pivotal role in both decelerating the progression of the curve and reducing the already increased magnitude of the curve.